Increased Expression of CSF-1 Associates With Poor Prognosis of Patients With Gastric Cancer Undergoing Gastrectomy. Issue 9 (March 2016) - Liu, Hao; Zhang, Heng; Shen, Zhenbin; Lin, Chao; Wang, Xuefei; Qin, Jing; Qin, Xinyu; Xu, Jiejie; Sun, Yihong
Abstract : Abstract: Clinical significance of diametrically polarized tumor-associated macrophages in gastric cancer has been elucidated in our previous study, whereas the role of cytokines that orchestrate tumor-associated macrophages polarization in gastric cancer remains elusive. The study aims to evaluate the prognostic value of colony-stimulating factor-1 expression in patients with gastric cancer. We examined the colony-stimulating factor-1 expression in tumor tissues by immunohistochemical staining in retrospectively enrolled 365 patients with gastric cancer undergoing gastrectomy at Zhongshan Hospital during 2008. Kaplan–Meier analysis and Cox regression models were used to evaluate the prognostic value of colony-stimulating factor-1 expression and its association with clinicopathological factors. A predictive nomogram by integrating colony-stimulating factor-1 expression with the TNM staging system was generated for overall survival evaluation of the patients. High colony-stimulating factor-1 expression predicted an unfavorable outcome in gastric cancer. The colony-stimulating factor-1 expression in tumor tissue could give a further discrimination for the prognosis of gastric cancer patients. Cox multivariate analysis identified the colony-stimulating factor-1 expression as an independent prognostic factor. The generated nomogram performed well in predicting the 3- and 5-year overall survival of gastric cancer patients. The colony-stimulating factor-1 is a potential independent adverse prognosticator for gastric cancer patients, which could be integrated with the tumor-associated macrophages staging system to improve the predictive accuracy for overall survival, especially in advanced tumors. Abstract : Supplemental Digital Content is available in the text